Kualitas Pelayanan Terhadap Kepuasan Pendonor Darah: Service Quality On The Blood Donors Satisfaction - Arif Tirtana; Marchiana Priska Idang; Ikrimah Nafilata (Journal of Health, 2024)
Service quality is an action that plays an important role in a health service institution. This study aims to determine the quality of donor selection and blood collection services on the satisfaction of blood donors in PMI Yogyakarta Special Region. This type of research is quantitative research with a cross sectional approach. The population in this study is voluntary blood donors who donate blood at PMI and have met the criteria for donor selection and blood collection. Sampling is done by Accidental sampling technique. The study population is all voluntary blood donors who came to UDD PMI Sleman Regency and UDD PMI Kota in August 2023. With the number of samples used in this study is 100 respondents. The data collection technique used in this study was using a questionnaire with a Likert scale. Data analysis techniques carried out using statistical test analysis using chi square. Based on the analysis of the data obtained, the characteristics of male blood donors were obtained as many as 79 people (79%). The results of donor satisfaction were obtained 87 (87%) very satisfied, based on donor selection services 51 (51%) Appropriate and blood services 53 (53%) in accordance with donor satisfaction. The results of the chi-square test were obtained in donor selection obtained p-veliu results (0.002) < 0.05 and in the results of the chi-square test blood draw obtained p-veliu results (0.154) > 0.05. This means that blood donor satisfaction is influenced by the quality of donor selection services and donor satisfaction is not influenced by the quality of blood collection services.